Atypical employment relationships and whistleblower status in terms of whistleblowing axiology - Łaguna, Łukasz (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
Narrowing the phenomenon of atypical employment relations to civil law employment, the author poses the following research hypotheses, which will be analyzed in this text: “Directive (EU) 2019/1937 of the European Parliament and of the Council of October 23, 2019 on the protection of whistleblowers does not distinguish between the rights of employees and those providing paid work on a basis other than an employment contract” and “The axiology, as well as the laws that are the source of whistleblowing and the Directive itself guarantee the right to report violations to all persons, regardless of the basis of employment.” Equally importantly, despite the introduction of analogous mechanisms at the substantive legal level, neither the Directive nor the Code of Civil Procedure guarantees non-employees preferential rights of redress compared to employees’ procedural rights. The study’s analysis shows that all of the above research hypotheses are true.